Wood adhesives / Nurul Hidayah Shafie - Shafie, Nurul Hidayah (2008)
This library research review what the adhesives are their types and the function of the wood adhesive. The research, shows that there are two category of adhesives. These are thermoplastic and thermosetting. Value of MOR, MOE and IB is increasing when more of adhesives are added in most penal product. Mixing content in each and every type of adhesive are different. Therefore, only certain adhesive will give food bonding for certain wood product.